Exploring the cyber world: the innovation of the cristal booklet to improve speaking literacy skills and critical thinking for elementary school students - Esty Yuliana Rabiah Aswadah; Nurul Istiq'faroh; Wahyu Sukartiningsih (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This study aims to examine the contribution of the CRISTAL Booklet (Critical Reading, Interactive Speaking, and Technology-Assisted Learning) to improving the speaking literacy and critical thinking skills of fifth-grade students who participated in the study. Speaking, literacy, and critical thinking are important skills that students need to develop. However, there are still challenges in applying these skills in the classroom. The CRISTAL Booklet was designed as a multimodal learning medium that combines critical reading, interactive speaking, and technology to enrich students’ learning experiences. This study used a quantitative approach with a one-group pretest-posttest research design. The participants were fifth-grade students from an elementary school. The research instruments included a pretest and a posttest to measure students’ speaking literacy and critical thinking skills. The results showed that the CRISTAL Booklet improved students’ speaking literacy and critical thinking skills, with a significant difference between pretest and posttest scores. Overall, the findings indicate that the CRISTAL Booklet can be used as an innovative and effective learning medium to improve speaking literacy and critical thinking skills among elementary school students.